12-week melatonin administration had no effect on diabetes risk markers and fat intake in overweight women night workers - de Sousa, Carlos Alberto Rodrigues; Nogueira, Luciana Fidalgo; Cipolla-Neto, José; Moreno, Claudia Roberta de Castro; Marqueze, Elaine Cristina (Frontiers in Nutrition, 2024)
Interactions between circadian clocks and key mediators of chronic low-grade inflammation associated with fat consumption may be important in maintaining metabolic homeostasis and may pose a risk for the development of obesity-associated comorbidities, especially type 2 diabetes (T2DM).The aims of the present study were to evaluate the effects of melatonin administration on diabetes risk markers according to dietary lipid profile (pro-inflammatory versus anti-inflammatory) in excessive weight night workers, and to determine the effect of administration on fat consumption profile.Methods: A randomized, controlled, double-blind, crossover clinical trial involving 27 nursing professionals working permanent night shifts under a 12x36-hour system. The melatonin group (12 weeks) used synthetic melatonin (3 mg) only on days off and between shifts, while the placebo group (12 weeks) was instructed to take a placebo, also on days off and between shifts. For inflammatory characteristics, participants were divided into pro-inflammatory (saturated fats, trans fats and cholesterol) and anti-inflammatory (monounsaturated, polyunsaturated fats and EPA+DHA) groups according to fatty acid determinations. At baseline and at the end of each phase, blood glucose, insulin, glycosylated hemoglobin plasma concentrations were collected, and HOMA-IR was calculated. This is a provisional file, not the final typeset article Conclusion: Melatonin administration for 12 weeks had no effect on T2DM risk markers according to dietary lipid profile (pro-inflammatory or anti-inflammatory potential) in excessive weight night workers. Among the limitations of the study include the fact that the low dose may have influenced the results expected in the hypothesis, and individual adaptations to night work were not evaluated. The insights discussed are important for future research investigating the influence of melatonin and fats considered anti-or pro-inflammatory on glucose and insulin homeostasis related to night work.